Social Media as a Catalyzer of Social Change Among Generation Z in the Modern Era - Perianto Rahul Pratama (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to examine social issues where social media influences social change among generation Z in the modern era. Social media has become an important element in everyday life, especially for generation Z who grew up in the digital era. As the group most familiar with technology, generation Z uses social media not only to interact and share information, but also as a tool to drive social change. This article aims to examine how social media acts as a catalyst for social change among generation Z. This study uses a qualitative approach by collecting data through literature studies and observations of current social media. The results show that social media provides a platform for generation Z to voice opinions, organize social movements, and fight for social, political, and environmental issues. Social media also facilitates the rapid dissemination of information, allowing generation Z to be more sensitive to various issues and play an active role in various changes. However, there are challenges related to the negative impacts of using social media, such as inaccurate information and increasingly sharp polarity. In conclusion, social media does play a big role as a catalyst for social change, but it also requires responsibility in its use.